Development of A Clinical Prediction Model for Oxytocin Resistance During Labor: A Prospective Cohort Study - Hemasa Gul, Huma Gul, Fatima Rehman, Naila (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Oxytocin resistance is an emerging clinical concept defined by inadequate uterine response despite escalating doses of exogenous oxytocin. It underlies a substantial proportion of failed inductions, prolonged labor, and unplanned cesarean deliveries. No validated bedside prediction model exists, particularly in South Asian settings. Materials and Methods: A prospective cohort study was conducted over an 18-months period from January 2022 to June 2023 in the Department of Obstetrics and Gynecology at Mardan Medical Complex, Mardan, Pakistan. A total of 420 women with singleton term pregnancies undergoing oxytocin induction or augmentation of labor were enrolled. Oxytocin resistance was defined as the requirement for oxytocin infusion rates exceeding 40 mIU/min without achieving adequate uterine activity or cervical progression. The primary outcome measures included total oxytocin dose, failed induction, cesarean delivery, and prolonged labor (>18 hours). A multivariate logistic regression model was developed to predict oxytocin resistance, and its discriminative ability was evaluated using the area under the receiver operating characteristic curve (AUC–ROC). Results: Of 420 participants, 112 (26.7%) met criteria for oxytocin resistance. Independent predictors were Bishop score ≤4 (OR 4.8, 95% CI 2.9–7.9), nulliparity (OR 3.2, 95% CI 1.8–5.7), BMI ≥30 kg/m² (OR 2.6, 95% CI 1.5–4.4), gestational age ≥41 weeks (OR 2.1, 95% CI 1.2–3.7), and prior oxytocin exposure (OR 1.9, 95% CI 1.1–3.3). The model achieved an AUC-ROC of 0.83 (95% CI 0.78–0.88). Oxytocin-resistant women had significantly higher rates of cesarean delivery (61.6% vs. 18.2%, p<0.001) and prolonged labor (54.5% vs. 9.1%, p<0.001). Conclusions: A five-variable bedside prediction model demonstrates good discrimination for oxytocin resistance and could guide pre-induction risk stratification. Multicenter external validation is warranted. Keywords: Oxytocin resistance; labor induction; cesarean section; failed induction; uterine contractility; prediction model; Bishop score; prolonged labor